The infrastructure investment effect and transportation sector toward economic growth in Indonesia - NurulIstifadah, Pascalia Rista Indah R., (Opción, 2020)
The success of a country’s economic development is identified by its economic growth, one of which is infrastructure investment and physical transportation sector. This research aims to analyze the effect of infrastructure investment and transportation sector toward economic growth in Indonesia. This research employed a quantitative approach based on time series analysis and Vector Autoregression analysis. Infrastructure investment significantly affected economic growth in Indonesia. In addition, it has a reciprocal correlation with economic growth. Meanwhile, land and sea transportation positively affected economic growth in Indonesia.